Analysis of X‐inactivation status in a Rett syndrome natural history study cohort. Issue 5 (23rd March 2022) - Fang, Xiaolan; Butler, Kameryn M.; Abidi, Fatima; Gass, Jennifer; Beisang, Arthur; Feyma, Timothy; Ryther, Robin C.; Standridge, Shannon; Heydemann, Peter; Jones, Mary; Haas, Richard; Lieberman, David N; et al.
Abstract: Background: Rett syndrome (RTT) is a rare neurodevelopmental disorder associated with pathogenic MECP2 variants. Because the MECP2 gene is subject to X‐chromosome inactivation (XCI), factors including MECP2 genotypic variation, tissue differences in XCI, and skewing of XCI all likely contribute to the clinical severity of individuals with RTT. Methods: We analyzed the XCI patterns from blood samples of 320 individuals and their mothers. It includes individuals with RTT ( n = 287) and other syndromes sharing overlapping phenotypes with RTT (such as CDKL5 Deficiency Disorder [CDD, n = 16]). XCI status in each proband/mother duo and the parental origin of the preferentially inactivated X chromosome were analyzed. Results: The average XCI ratio in probands was slightly increased compared to their unaffected mothers (73% vs. 69%, p = .0006). Among the duos with informative XCI data, the majority of individuals with classic RTT had their paternal allele preferentially inactivated ( n = 180/220, 82%). In sharp contrast, individuals with CDD had their maternal allele preferentially inactivated ( n = 10/12, 83%). Our data indicate a weak positive correlation between XCI skewing ratio and clinical severity scale (CSS) scores in classic RTT patients with maternal allele preferentially inactivated XCI ( r s = 0.35, n = 40), but not in those with paternal allele preferentially inactivated XCI ( r s = −0.06, n = 180). The most frequent MECP2 pathogenic variants were enriched in individuals with highly/moderately skewed XCI patterns, suggesting an association with higher levels of XCI skewing. Conclusion: These results extend our understanding of the pathogenesis of RTT and other syndromes with overlapping clinical features by providing insight into the both XCI and the preferential XCI of parental alleles. Abstract : X chromosome inactivation (XCI) analysis of 320 proband‐mother duos showed that majority of individuals with classic Rett syndrome had their paternal allele preferentially inactivated, while, in sharp contrast, majority of individuals with CDKL5 Deficiency Disorder had their maternal allele preferentially inactivated. Our data also indicated that in individuals with classic Rett syndrome, there is a weak positive correlation between XCI skewing ratio and clinical severity of individuals with maternal allele preferentially inactivated, but not in those with paternal allele preferentially inactivated.